The influence of reaming velocity during preparation of the femoral canal: an in vitro analysis of two straight femoral revision stems with a fluted tapered design - Bischel, Oliver E.; Seeger, Jörn Bengt; Jung, Matthias; Dörfler, Stefan; Höppchen, Arnold; Jahnke, Alexander; Jakubowitz, Eike (Bioengineering, 2025)
Background: The use of tapered fluted revision stems has been shown to be reliable and safe. Primary stability is mandatory for a long-lasting fixation between bone and a prosthesis. Nevertheless, aseptic loosening due to insufficient primary stability occurs and may be related to technically improper preparation of the femoral canal. Instructions of manufacturers are heterogeneous regarding preparation of implant beds. Questions/Purposes: Does speed or the design of the reamer influence the accuracy of the implant bed and, consecutively, primary stability? Materials and Methods: A test foam with an elastic moduli and pressure resistance similar to that of cancellous bone was used. The medullary canal was prepared with the use of reamers of two different straight and tapered femoral revision devices. Three different rotational speeds were used for preparation. After preparation, primary stability was measured and fixating characteristics were derived. Results: Sufficient primary stability was achievable by all three preparation methods but fixating characteristics were different. Significantly higher micro-motions were detected near the tip of the prosthesis compared to those at all more proximal measuring points. Reaming with high velocity resulted in significantly higher micro-motions compared to that with mid- or low-speed burring. Conclusions: Different preparation methods may be one explanation for the range of reported survivorship data of the two devices with aseptic loosening as the end point. The precision of the implant bed and fixating characteristics were best after reaming with lower velocity. Superior but not significantly better fixation characteristics were achieved with the monobloc stem compared to those with the modular device.